Bioautographic profile as standard reference for qualitative analysis of the efficacy of herbs as antiseptic and antioxidant - Mohd Hassan, Norazian; Abdul Latif, Aina Fairuz; Sarbini, Hasdayanti; Mohd Yusof, Sha'erah; Md Taib, Nurhaya (2008)
This study was designed to develop a standard reference for qualitative analysis of the efficacy of herbs as antiseptic and antioxidant. Its main aim was to validate the authenticity of the herbal materials and quality control of their pharmaceutical herbal preparations. A method combining bioautographic assay and thin layer chromatography (TLC) analysis was employed to detect the antioxidant and antiseptic biomarkers and to obtain the TLC profile, respectively. The herbal extracts were subjected to TLC analysis on silica gel plates and each separated compound was visualized by various detection methods. Extracts of three selected herbs were studied and they were Piper betle L. (leaves), Ficus deltoidea Jack (leaves) and Ruta angustifolia Pers. (aerial parts). Antiseptic biomarkers were detected by using bioautographic agar overlay assay against selected standard bacterial and fungal strains, namely Staphylococcus aureus, Escherichia coli, Candida albicans, Microsporum cannis and Trichophyton rubrum. Antioxidant biomarkers were examined using TLC and DPPH staining assay. The complete bioautographic profile which included the antioxidant and antiseptic biomarkers with their TLC characteristics could be used as standard reference for qualitative analysis on the efficacy of these herbs and their herbal preparations. This method would also be applicable to other herbs for efficacy analysis.